HUBUNGAN LOCUS OF CONTROL DENGAN BURNOUT PADA PERAWAT DI INSTALANSI GAWAT DARURAT RSUD PASAR REBO - Mentari Elisabeth Tinambunan (2021)
Nurses, as the most health human resources in hospitals, experience the highest burnout rates. Locus of Control is rated good at controlling burnout felt by nurses. The purpose of this study was to determine the relationship of Locus of Control with Burnout as well as the dominant factors that affect Burnout in nurses of Emergency Installation of Pasar Rebo Hospital. This study uses a cross sectional design. The research was conducted to 29 nurses, with total sampling techniques. Data analysis uses Product Moment Correlation, Pearson Correlation Test, and Multiple Linear Regressions. The results found that the majority of nurses (n=29) were in mild burnout levels. Test Result F obtained F count of 7,266 with p value= 0.003 means that Internal and External Locus of Control simultaneously affect Burnout on nurses in the Emergency Installation of Pasar Rebo Hospital. However, partially only the External Locus of Control affects Burnout (p value= 0.001). The conclusion of this study locus of external control is related to burnout in nurses in the Emergency Installation of Pasar Rebo Hospital. It's expected that Pasar Rebo Hospital creates a working environment and good leadership qualities in preventing and handling more severe burnouts.